Accounting graduates and the capabilities that count: Perceptions of graduates, employers and Accounting academics in four Australian universities - Oliver, Beverley; Whelan, Barbara; Hunt, L.; Hammer, S. (Curtin University, 2011)
The higher education sector in Australia is moving rapidly towards greater accountability in regard to graduate employability outcomes. Currently, data on new graduates’ self-reported generic skills and employment status provide the evidence base for universities to make judgements about the effectiveness of curricula in preparing students for employment. This paper discusses alternative sources of evidence, namely the Graduate Employability Indicators (GEI) - a suite of three online surveys designed to supplement current indicators. They are designed to gather and report graduate, employer and course (teaching) team perceptions of the achievement and importance of graduate capabilities within specific degree programs. In 2009 and 2010, the surveys were administered to stakeholder groups associated with Accounting degrees in four Australian universities. In total, 316 graduates, 99 employers and 51 members of the course teaching teams responded to the surveys. This report presents the aggregated results from the trial. These suggest that the fourteen capabilities at the heart of the GEI are considered important, and that both quantitative and qualitative items facilitate the reporting of essential information. Both Accounting employers and teaching staff consider that important capabilities need to be better demonstrated by new graduates. The graduates themselves identified ways in which their courses can be improved to enhance their early professional success.An importance-performance analysis suggests prioritising particular capabilities for immediate attention in particular, work related knowledge and skills, writing clearly and effectively, thinking critically and analytically, solving complex, real-world problems and developing general industry awareness. This paper suggests that an enhanced industry focus might be effected through authentic assessment tasks, and clear identification of the capabilities developed through the curriculum.